The aetiology, risk factors and outcome of acute kidney injury in patients requiring kidney replacement therapy – a prospective single center experience - Abbas, Rabeea; Elahi, Tabassum; Manan, Shumaila; Younas, Shafique (Journal of the Pakistan Medical Association, 2023)
Objective: To find out the causes, associated leading factors and impact of kidney replacement therapy on patients hospitalised for acute kidney injury in a tertiary care setting. Method: The prospective, cross-sectional study was conducted at the Sindh Institute of Urology and Transplantation, Karachi, from January 1 to March 31, 2022, and comprised patients of either gender aged 18 or more years presenting with acute kidney injury as per the Kidney Disease Improving Global Outcomes criteria and required kidney replacement therapy. Complete, partial or no recovery was the main outcome parameter noted at the end of 90 days. Possible aetiologies were identified and categorised as pre-renal, renal and post-renal aetiologies. Risk factors for acute kidney injury were recorded, including age, gender and co-morbidities. Data was analysed using SPSS 22. Results: Of the 210 patients with mean age 46.1±14.24 years, 109(52%) were males and 101(48%) were females (p>0.05). Hypertension was the most common comorbidity 98(46.8%), followed by diabetes mellitus 75(35.7%) and underlying chronic kidney disease 55(26.2%). Multiple therapeutic interventions were required, including vasopressors in 101(48.1%) patients and mechanical ventilation in 31(14.8%). Renal failure due to intrinsic renal aetiology was the most common 98(46.7%), followed by post-renal aetiology 61(29%). There was no significant association between outcomes and aetiologies (p>0.05). There was increase in chronic kidney disease cases from 55(26.2%) patients at baseline to 107(50.9%) at the end of 90 days. Complete recovery was noted in 71(33.8%) patients, partial in 73(34.76%), no recovery in 34(16.1%) patients who required maintenance kidney replacement therapy, and 32(15.2%) patients died. Conclusion: Complete recovery after 90 days of kidney replacement therapy was observed in one-third of the patients. Intrinsic renal aetiology was the most prevalent, and hypertension was the most common comorbidity. Key Words: AKI, CKD, KRT.